Importance of Shrines in the Development of Historical and Cultural Tourism (Eurasian Scientific Herald, 2023)
This article shows the role of pilgrimage tourism in the development of the economy in the Fergana Valley. Also, the current state of tourism in the region is analyzed, and conclusions, suggestions and recommendations are given for its future development.